Neonatal anoxia in rats: hippocampal cellular and subcellular changes related to cell death and spatial memory - Takada, S. H.; Dos Santos Haemmerle, C. A.; Motta-Teixeira, L. C.; Machado-Nils, A. V.; Lee, V. Y.; Takase, L. F.; Cruz-Rizzolo, R. J. [UNESP]; Kihara, A. H.; Xavier, G. F.; Watanabe, I. -S.; Nogueira, M. I. (Elsevier B.V., 2015)
Neonatal anoxia in rodents has been used to understand brain changes and cognitive dysfunction following asphyxia. This study investigated the time-course of cellular and subcellular changes and hippocampal cell death in a non-invasive model of anoxia in neonatal rats, using Terminal deoxynucleotidyl transferase-mediated dUTP Nick End Labeling (TUNEL) to reveal DNA fragmentation, Fluoro-Jade(R) B (FJB) to show degenerating neurons, cleaved caspase-3 immunohistochemistry (IHC) to detect cells undergoing apoptosis, and transmission electron microscopy (TEM) to reveal fine ultrastructural changes related to cell death. Anoxia was induced by exposing postnatal day 1 (P1) pups to a flow of 100% gaseous nitrogen for 25 min in a chamber maintained at 37 degrees C. Control rats were similarly exposed to this chamber but with air flow instead of nitrogen. Brain changes following anoxia were evaluated at postnatal days 2, 14, 21 and 60 (P2, P14, P21 and P60). In addition, spatial reference memory following anoxia and control treatments was evaluated in the Morris water maze, starting at P60. Compared to their respective controls, P2 anoxic rats exhibited (1) higher TUNEL labeling in cornus ammonis (CA) 1 and the dentate gyrus (DG), (2) higher FJB-positive cells in the CA2-3, and (3) somato-dendritic swelling, mitochondrial injury and chromatin condensation in irregular bodies, as well as other subcellular features indicating apoptosis, necrosis, autophagy and excitotoxicity in the CA1, CA2-3 and DG, as revealed by TEM. At P14, P21 and P60, both groups showed small numbers of TUNEL-positive and FJB-positive cells. Stereological analysis at P2, P14, P21 and P60 revealed a lack of significant differences in cleaved caspase-3 IHC between anoxic and control subjects. These results suggest that the type of hippocampal cell death following neonatal anoxia is likely independent of caspase-3 activation. Neonatal anoxia induced deficits in acquisition and performance of spatial reference memory in the Morris water maze task. Compared to control subjects, anoxic animals exhibited increased latencies and path lengths to reach the platform, as well as decreased searching specifically for the platform location. In contrast, no significant differences were observed for swimming speeds and frequency within the target quadrant. Together, these behavioral results indicate that the poorer performance by anoxic subjects is related to spatial memory deficits and not to sensory or motor deficits. Therefore, this model of neonatal anoxia in rats induces hippocampal changes that result in cell losses and impaired hippocampal function, and these changes are likely related to spatial memory deficits in adulthood. (C) 2014 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: Apoptosis; Hippocampal cell death; Spatial memory; Neonatal hypoxia; Asphyxia; Transmission electron microscopy